Martyrdom Syndrome: Reading Acts 7:54-8:1 As A Critique of Christian Leaders - Afaradi, Asep; Pantaow, Milton (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
This study analyzes the Martyrdom Syndrome in Christian leadership by interpreting Acts 7:54-8:1 as a critique of leaders who use the suffering narrative to gain legitimacy and authority. This syndrome refers to the tendency of individuals to portray themselves as victims to gain sympathy, support, and justification for their leadership. The study employs a qualitative, exegetical approach to the martyrdom of Stephen, which is often contrasted with authentic leadership in the Christian tradition. The findings reveal that true martyrdom in Acts is not used as a tool for manipulation but as a testimony of faith rooted in the truth of the Gospel. In contrast, leaders trapped in the martyrdom syndrome tend to foster unhealthy relationships with their followers, relying on personal suffering as spiritual legitimacy. This study affirms that authentic Christian leadership is not based on exploiting the suffering narrative but on exemplary conduct, service, and moral integrity. Thus, this research contributes to a deeper understanding of responsible Christian leadership and critiques deviant leadership practices in ecclesial and social contexts.